Diseases of the parathyroid glands - Licata, Angelo A. (Springer New York :, 2012)
For medical practitioners at all stages of experience, diseases of the parathyroid glands are not easily deciphered.  There are many subtleties to its pathology and diagnosis. Today, the wealth of new information from molecular medicine makes it very challenging for the individual practitioner to have a complete picture of these entities.  Diseases of the Parathyroid Glands addresses these issues by offering a concise, user-friendly text that provides state-of-the-art background on bone and mineral physiology and its regulation and couples this to a variety of clinical topics of parathyroid gland pathology. Introductory chapters cover calcium regulation and parathyroid gland physiology, drawing upon many of the new aspects of glandular control mechanisms beyond the classical ones associated with calcium alone. The majority of the text covers clinical problems.  Although most chapters address problems in adult medicine, three separate chapters are devoted to pediatric problems of hyper- and hypoparathyroidsm and parathormone resistance states.  In addition, there are several chapters on less common but equally challenging problems such as parathyroid cancer, calciphylaxis, cystic lesions of the glands, and ectopic glandular disease. The final chapters detail the techniques of parathyroid gland imaging and surgical treatment.   Practical and an invaluable addition to the literature, Diseases of the Parathyroid Glands is an indispensable reference for anyone interested in parathyroid disease. 1. Molecular Mechanisms of Parathyroid Hormone Synthesis -- 2. Regulation of Calcium and Phosphate Metabolism -- 3. Diagnosis and Treatment of the Patient with Abnormal Calcium -- 4. The Calcium-Sensing Receptor: Physiology and Pathophysiology -- 5. New Concepts for Primary and Secondary Hyperparathyroidism -- 6. Calcific Uremic Arteriolopathy (Calciphylaxis) -- 7. Cystic Parathyroid Lesions -- 8. Parathyroid Cancer -- 9. Biochemistry, Physiology and Pathophysiology of Parathyroid Hormone-Related Peptide -- 10. Ectopic Parathyroid Glands -- 11. Hyperparathyroidism in Multiple Endocrine Neoplasia -- 12. Familial Hypocalciuric Hypercalcemia -- 13. Hyperparathyroidism-Jaw Tumor Syndrome -- 14. Hypoparathyroidism and Pseudohypoparathyroidism -- 15. Primary Hyperparathyroidism in Neonates and Children -- 16. Hypoparathyroidism in Children -- 17. Parathormone Resistance in Children -- 18. The Use of Ultrasonography in the Management of Parathyroid Diseases -- 19. Imaging in Parathyroid Diseases -- 20. Parathyroid Surgery.